The RETRIEVE checklist for studies reporting the elicitation of stated preferences for child health-related quality of life - Bailey, C; Howell, M; Raghunandan, R; Dalziel, K; Howard, K; Mulhern, B; Petrou, S; Rowen, D; Salisbury, A; Viney, R; Lancsar, E; Devlin, N (Springer, 2024)
Background: Recent systematic reviews show varying methods for eliciting, modelling, and reporting preference-based values for child health-related quality-of-life (HRQoL) outcomes, thus producing value sets with different characteristics. Reporting in many of the reviewed studies was found to be incomplete and inconsistent, making them difficult to assess. Checklists can help to improve standards of reporting; however, existing checklists do not address methodological issues for valuing child HRQoL. Existing checklists also focus on reporting methods and processes used in developing HRQoL values, with less focus on reporting of the values’ key characteristics and properties. We aimed to develop a checklist for studies generating values for child HRQoL, including for disease-specific states and value sets for generic child HRQoL instruments. Development: A conceptual model provided a structure for grouping items into five modules. Potential items were sourced from an adult HRQoL checklist review, with additional items specific to children developed using recent reviews. Checklist items were reduced by eliminating duplication and overlap, then refined for relevance and clarity via an iterative process. Long and short checklist versions were produced for different user needs. The resulting long RETRIEVE contains 83 items, with modules for reporting methods (A–D) and characteristics of values (E), for researchers planning and reporting child health valuation studies. The short RETRIEVE contains 14 items for decision makers or researchers choosing value sets. Conclusion: Applying the RETRIEVE checklists to relevant studies suggests feasibility. RETRIEVE has the potential to improve completeness in the reporting of preference-based values for child HRQOL outcomes and to improve assessment of preference-based value sets.